2020
DOI: 10.3389/fmicb.2020.582022
|View full text |Cite
|
Sign up to set email alerts
|

The 23S Ribosomal RNA From Pyrococcus furiosus Is Circularly Permuted

Abstract: Synthesis and assembly of ribosomal components are fundamental cellular processes and generally well-conserved within the main groups of organisms. Yet, provocative variations to the general schemes exist. We have discovered an unusual processing pathway of pre-rRNA in extreme thermophilic archaea exemplified by Pyrococcus furiosus. The large subunit (LSU) rRNA is produced as a circularly permuted form through circularization followed by excision of Helix 98. As a consequence, the terminal domain VII that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 61 publications
1
14
2
Order By: Relevance
“…Stabilization of interactions between the 5′ and 3′ ends of the LSU rRNA during early ribosome assembly is conserved from bacteria to eukaryotes, highlighting its importance for ribosome assembly. Intriguingly, the 23S rRNA of thermophilic archaea Pyrococcus furiosus is even circularly permutated 72 . Consistent with this, our data indicate that in the absence of Dbp7, when recruitment of uL3 is impaired, pre-60S particles are degraded, likely having not fulfilled a necessary quality control requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization of interactions between the 5′ and 3′ ends of the LSU rRNA during early ribosome assembly is conserved from bacteria to eukaryotes, highlighting its importance for ribosome assembly. Intriguingly, the 23S rRNA of thermophilic archaea Pyrococcus furiosus is even circularly permutated 72 . Consistent with this, our data indicate that in the absence of Dbp7, when recruitment of uL3 is impaired, pre-60S particles are degraded, likely having not fulfilled a necessary quality control requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, and as discussed, the ribosome biogenesis sequence homologs and r-proteins are not ubiquitously distributed across archaea. Therefore, it is of interest to define the extent of archaeal ribosome biogenesis diversity and functional adaptation (Seistrup et al, 2017;Birkedal et al, 2020;Sas-Chen et al, 2020;Knüppel et al, 2021). Additionally, future metagenomics analyses will certainly increase the numbers of newly identified archaea.…”
Section: Perspectives and Outlookmentioning
confidence: 99%
“…A first set of roles, which is often at least partially modification independent, is in facilitating the multi-step rRNA maturation. rRNA is typically transcribed as a single precursor, which is subsequently subject to complex exo-and endonucleolytic cleavage events, giving rise to the large and small rRNA subunits that concomitantly need to fold and assemble into their proper structure (Birkedal et al 2020;Aubert et al 2018;Sloan et al 2016a;Polikanov et al 2015;Jiang, Seo, and Chow 2016;Demirci et al 2010). Loss-of-function assays have revealed that some rRNA modifying enzymes are required for this processing (D. Lafontaine, Vandenhaute, and Tollervey 1995;Liang, Liu, and Fournier 2009;Sharma, Yang, et al 2013) and their loss results in accumulation of ribosome precursors.…”
Section: Rrna Modifications: Functionsmentioning
confidence: 99%